Peculiarities of functional and motor preparedness of pupils of 7-8 classes - Іващенко, О. В. (Physical Education Theory and Methodology, 2014)
The purpose of research — to determine the sexual features of functional and motor preparedness of pupils of 7-8 classes. Material and methods. To achieve the objectives following methods were used: analysis of scientific and methodical literature, teacher testing and statistical methods. The study involved children: 24 people. 7th grade, 35 — 8th grade; Girls 31 people. 7th grade, 14 — 8th grade. Results of the study. The analysis shows that between boys and girls in grades 7 functional tests, a statistically significant difference (p<0,001). For the functional state of the respiratory and circulatory functions boys 7th grade are assessed as healthy, untrained; Serkin at trial — as having a latent form of heart failure. Statistically significant differences between boys and girls 8 classes are observed in the tests № 3-8, characterized by its own power, speed strength and coordination preparedness (p<0.001). According to the results of other motor tests differences between the mean values are not statistically significant (p>0,05). Conclusions. Sexual peculiarities of motor preparedness of students seventh grade is the level of development of power abilities and capacity for assessing the perception of the power of motion parameters; eighth-grade students - the ability to assessing the perception of motion and force parameters of static power.